Getting lost (and found) in supervision: an ethnodrama. (8th May 2017) - French, Amanda; Kendall, Alex
Abstract : Purpose: This paper aims to offer an innovative approach to reflecting on research and practice around doctoral study and supervision. In the opening section of the paper, the authors discuss the idea that academic development as a doctoral candidate is concerned with how researchers write themselves into being as certain kinds of researchers, and how, in doing so, they become a character, like their supervisors, in the "figured world" of their research. This process of "becoming" can, the authors argue, be nurtured or hindered by different kinds of supervision practices. Design/methodology/approach: With regard to the authors' own experiences of doctoral supervision, the paper explores how their use of post-qualitative practices and methodologies encouraged new forms of intersubjectivity and academic development as their supervisory relationship advanced alongside the thesis itself. Findings: The authors present the script of an ethnodrama (Saldana, 2111) which they wrote and performed on a number of occasions, as an alternative way of expressing their experiences of being in a relationship as doctoral supervisor and supervisor. Research limitations/implications: This choice of ethnodrama emerged out of a frustration with what the authors felt were increasingly predictable ways of discussing and reflecting upon the philosophy, content and assessment methods of postgraduate research and supervision across the educational disciplines. Originality/value: The authors hope that their exploration of the imaginative spaces created through doctoral supervision will encourage other postgraduates and their supervisors to experiment with working creatively across interdisciplinary spaces and creating radical and even risky ways of mediating and sharing postgraduate teaching and learning relationships.